2023
DOI: 10.4081/monaldi.2023.2748
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous lung cancer presenting with small cell carcinoma and squamous cell lung carcinoma: a case report

Emanuele Stirpe,
Floriana Bardaro,
Johanna Koehl

Abstract: Synchronous multiple primary lung cancers are separate tumors presenting at the same time with different histology. We present a rare case of a 64-year-old patient with a combination of small-cell lung carcinoma (SCLC) and squamous carcinoma in two different sites with metastasis of SCLC in the mediastinal lymph node. The SCLC diagnosis was performed via bronchoscopy, and the other diagnosis via CT-guided transthoracic biopsy. It is often difficult to distinguish a synchronous tumor from intrapulmonary metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Distinguishing between a multi-center lung cancer and a primary tumor in a different organ becomes challenging when there is more than one primary lung tumor. 4 Roughly 60% of sMPLC consist of squamous cell carcinomas, with 60% of these instances demonstrating tumors of identical histologic type. 5 Trousse et al demonstrated that the presence of SCC in combination constituted 28.8% among 125 study patients with sMPLC.…”
Section: Early Access Chest Disease Reports Case Reportmentioning
confidence: 99%
“…Distinguishing between a multi-center lung cancer and a primary tumor in a different organ becomes challenging when there is more than one primary lung tumor. 4 Roughly 60% of sMPLC consist of squamous cell carcinomas, with 60% of these instances demonstrating tumors of identical histologic type. 5 Trousse et al demonstrated that the presence of SCC in combination constituted 28.8% among 125 study patients with sMPLC.…”
Section: Early Access Chest Disease Reports Case Reportmentioning
confidence: 99%